Mapping status for river water quality of Sungai Perlis based on DOE-WQI - Arfah Adnin Hamdan (School of Environmental Engineering, University Malaysia Perlis, 2013)
A study was conducted to assess water quality at Sungai Perlis. The main objective of this this study is to built a mapping status for river water quality based on DOE-WQI by identify the water quality, level of pollution and pollution sources that would lead to pollution in the area.